1995
DOI: 10.1063/1.358681
|View full text |Cite
|
Sign up to set email alerts
|

Model for the substrate hole current based on thermionic hole emission from the anode during Fowler–Nordheim electron tunneling in n-channel metal-oxide-semiconductor field-effect transistors

Abstract: A model is proposed to explain the dependence of the substrate hole current in n-channel metal-oxide-semiconductor field-effect transistors (MOSFETs) on applied electric field and on oxide thickness. Two types of devices were prepared: n-channel MOSFETs with gate oxides of 67, 86, and 131 Å and p-channel MOSFETs in which gate oxide thicknesses were almost equal to those in the n-channel MOSFETs. The carrier-separation technique was used in the p-channel MOSFETs, and the average energy of hot electrons entering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…We assume that the positive charge responsible for erratic behaviors may origin from an Anode Hole Injection mechanism [7]: during erasing the FN electron current density creates hole/electron pairs at the anode by impact ionization. Part of the holes tunnels back to the floating gate and some of them may be trapped into the oxide.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the positive charge responsible for erratic behaviors may origin from an Anode Hole Injection mechanism [7]: during erasing the FN electron current density creates hole/electron pairs at the anode by impact ionization. Part of the holes tunnels back to the floating gate and some of them may be trapped into the oxide.…”
Section: Discussionmentioning
confidence: 99%
“…A report after the above, refuted this process of hole generation and concluded that the generation efficiency of photons with energy above the Si bandgap energy is 10 -4 times smaller than that of the electron-hole pairs by impact ionization [21]. The above studies, leads the author to believe that the hot holes from the anode are back injected into the oxide over the barrier [15,22]. After coming to the oxide valence band, the hole current follows the exp(-B/E) dependence of the FN tunnelling equation (1).…”
Section: Discussionmentioning
confidence: 95%
“…The resulting hole mass of 0.58m is the same as that obtained for p-4H-SiC MOS device in accumulation undergoing FN tunnelling of holes [2], where the Schottky barrier lowering does not change the tunnelling distance. This implies that Schottky barrier lowering in thin oxides of 5 to 10nm, in which the hot holes are injected into the oxide valence band by thermionic emission over the barrier is absent [15,22]. This is due to the fact that the generated hot holes due to impact ionization at the polysilicon anode of the electrons arriving from the cathode also have a thickness independent energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since oxide thickness of todayÕs Flash memories is in the range of 7-10 nm, it is difficult to assume that trapped holes may result as a consequence of impact ionization occurring in the oxide because this phenomenon is more likely to occur in thicker oxides. Therefore anode hole injection [21] has been assumed to be the main cause of hole injection during channel erase [22].…”
Section: Erratic Bitsmentioning
confidence: 99%